Renoprotective Effect of Laminaria japonica Polysaccharide in Adenine-Induced Chronic Renal Failure - Long, Miao (Molecules, 2019)
Chronic renal failure (CRF) is a major public health problem worldwide. In this work, we investigated the effects of a purified Laminaria japonica polysaccharide (LJP61A) on renal function using an adenine-induced CRF mice model. Results exhibited that adenine treatment caused serious renal pathological damages and elevation of serum creatinine and blood urea nitrogen of mice. However, these changes could be significantly reversed by the administration of LJP61A in a dose-dependent manner. Additionally, LJP61A could dramatically reduce weight loss, improve the urine biochemical index, and regulate the electrolyte disturbance of CRF mice. These results suggest that the renal function of adenine-induced CRF mice can be improved by LJP61A, which might be developed into a potential therapeutic agent for CRF patients.